Analisis penerapan manajemen risiko likuiditas dalam menjaga stabilitas keuangan bank - Aliyana, Ama Dwi (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the implementation of liquidity risk management in maintaining bank financial stability. Liquidity risk is one of the important risks faced by banks because it is related to the ability to meet short-term obligations. An imbalance between sources of funds and fund distribution can create liquidity pressure that has the potential to disrupt bank financial stability. Therefore, the implementation of effective liquidity risk management is required so that banks are able to maintain their financial condition. This study uses a qualitative method with a literature review approach sourced from various journals and previous studies related to liquidity risk management. The results show that the implementation of liquidity risk management is carried out through several stages, namely risk identification, risk measurement, risk monitoring, and risk control. Each of these stages plays a role in ensuring that bank liquidity availability is maintained. Proper implementation of liquidity risk management can improve the bank’s ability to meet its obligations, maintain public confidence, and support sustainable bank financial stability.